Lista Przebojów Programu Trzeciego - problemy statystyczne - Łapczyński, Artur; Niedźwiecki, Marek; Sokołowski, Andrzej (Radio 3 Hit List - Statistical Problems, 2005)
Radio 3 Hit List is the most popular weekly pop chart in Poland, based on the listeners votes. History, the most popular charts in the world and their place in the entertainment market is presented in the first part of the paper. Then the Radio 3 Hit List is characterised with the emphasis put on voting systems, chart rules and special features like "waiting room", "unlucky seven", etc. Special data base covering all weekly editions up to the end of 2003 has been prepared. More than 4000 songs, described by their chart run characteristics are then clustered. Groups are then characterized by averages and by typical representatives. Some other statistical problems are also addressed, like the distribution of popularity, chart survival curves, outliers, voting cheating, the efficienty of different voting systems and voting generators.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 57-70